Suitability of Dried Blood Spots for Accelerating Veterinary Biobank Collections and Identifying Metabolomics Biomarkers With Minimal Resources - Allaway, David; Alexander, Janet E.; Carvell-Miller, Laura J.; Reynolds, Rhiannon M.; Winder, Catherine L.; Weber, Ralf J. M.; Lloyd, Gavin R.; Southam, Andrew D.; Dunn, Warwick B. (Frontiers in Veterinary Science, 2022)
Biomarker discovery using biobanked samples collected in the veterinary clinic would deliver insights into the diverse population of pets and accelerate diagnostic development. The acquisition, preparation, processing and storage of biofluid samples in sufficient volumes, and at a quality suitable for later analysis, by the most suitable discovery methods, remains challenging. Metabolomics analysis is a valuable approach to detect health/disease phenotypes. Pre-processing changes during the preparation of plasma/serum samples may induce variability that may be overcome using dried blood spots (DBS). We report a proof of principle study using metabolite fingerprinting applying UHPLC-MS of plasma and DBS acquired from healthy adult dogs and cats (age range 1-9 years), representing each of 4 dog breeds (Labrador retriever, Beagle, Petit Basset Griffon Vendeen and Norfolk terrier) and the British domestic shorthair cat (n=10 per group). Blood samples (20µL and 40µL) for DBS were loaded onto filter paper, air-dried at room temperature (3 hours) and sealed and stored (4°C for ~72 hours) prior to storage at -80°C. Plasma from the same blood draw (250µL) was prepared and stored at -80°C within 1 hour of sampling. Metabolite fingerprinting of DBS and plasma produced similar numbers of metabolite features that had similar abilities to discriminate between biological classes and correctly assign blinded samples. These provide evidence that DBS, sampled in a manner amenable to application in-clinic/in-field processing, is a suitable sample for biomarker discovery using UHPLC-MS metabolomics. Further, given appropriate owner consent, the volumes tested (20-40µL) make the acquisition of remnant blood from blood samples drawn for other reasons available for biobanking and other research activities. Together, these make possible large-scale biobanking for veterinary samples, gaining sufficient material sooner and enabling quicker identification of biomarkers of interest.